The Chinese way of response to hospitality service failure: The effects of face and guanxi. (August 2016) - Li, Mimi; Qiu, Shangzhi (Charles); Liu, Zhaoping
Abstract: In this study, a quasi-experiment was conducted to investigate the effects of two significant cultural values, face and guanxi, on Chinese customers' behavioral responses to hospitality service failures. Hotel check-in process failure was used as the service encounter scenario. Based on the results of a multi-group structural equation modeling analysis, the study identified that concern for face can increase the intention to spread negative word-of-mouth information about service process failure experiences. In contrast, the existence of guanxi between hotels and customers can reduce the intention to terminate transactions or post negative online reviews. In addition, guanxi can moderate the influence that concern for face has on direct complaint intention. When guanxi exists, concern for face motivates customers to complain directly. Theoretical and managerial implications are discussed based on the findings.